Analysis of Unity3D Asset Store. Launch of a product, tactics to maximize sales. - Korchun, Denis (2017)
This thesis focuses on several topics. The first one is a description of Unity3D and its official marketplace - Asset Store, including reasons why the market is attractive for publishers. The second one aims at customers - their motivation for visiting the store and performing purchases. Also, it contains a brief analysis of Asset Store products value for customers based on game developer experience with using several products on a project. The third topic covers development of our own product over time, containing information on wide range of activities like competitors monitoring and analysis, as well as important decisions on further development taken. A path from a poorly performing product to the one of the most popular in a category is described. The last topic is focused on searching for additional ways to maximize publisher income from Asset Store. The aim of this work is to provide practical information on topics described above from two different, yet closely related point of views of both customer and publisher.